2022
DOI: 10.3390/f13040569
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Working Performance and Costs of Two Small-Scale Harvesting Systems for Medium Rotation Poplar Plantations

Abstract: Considering the increasing need to produce energy from renewable sources, the interest towards Medium Rotation Coppices (MRC) plantations has increased. One of the main issues that require tackling for the comprehensive sustainability of these plantations is related to the development of sustainable harvesting systems. Indeed, as a consequence of the average tree diameters at a breast height (dbh) of about 15 cm, single-pass harvesting typical of short rotation coppice is not applicable. Therefore, these plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Magagnotti and Spinelli (2011) reported a productivity of 1.9-3.0 m 3 PMH 1 for animal extraction in beech high forests, while a higher value of 4.0 m 3 PMH −1 was reported for extraction operations carried out by short wood system with a farm tractor equipped with frontal and rear loaders [46]. Obtained values are also in line with the range 3.2-5.0 m 3 PMH −1 reported by Vusić et al (2013) for winching with a small-scale skidder in a mixed hardwood stand in Croatia [47] and even higher than the 2.836 m 3 SMH −1 for winching extraction in a poplar plantation in Central Italy performed with a tractor and a winch of similar dimensions as the ones applied in the Pian Cansiglio and Mongiana study areas [48].…”
Section: Discussionsupporting
confidence: 83%
“…Magagnotti and Spinelli (2011) reported a productivity of 1.9-3.0 m 3 PMH 1 for animal extraction in beech high forests, while a higher value of 4.0 m 3 PMH −1 was reported for extraction operations carried out by short wood system with a farm tractor equipped with frontal and rear loaders [46]. Obtained values are also in line with the range 3.2-5.0 m 3 PMH −1 reported by Vusić et al (2013) for winching with a small-scale skidder in a mixed hardwood stand in Croatia [47] and even higher than the 2.836 m 3 SMH −1 for winching extraction in a poplar plantation in Central Italy performed with a tractor and a winch of similar dimensions as the ones applied in the Pian Cansiglio and Mongiana study areas [48].…”
Section: Discussionsupporting
confidence: 83%
“…This has been confirmed for both poplar and eucalyptus MRC plantations compared to SRC ones [ 50 , 69 ]. However it is worth highlighting that increasing the rotation time leads to higher dimensions for the stems to be harvested, thus no longer allowing for single-passage harvesting but requiring double-passage harvesting carried out with machinery specifically developed for forest management (chainsaw, feller-buncher, harvester, forwarder, cable skidder) [ 70 , 71 , 72 , 73 ]. Apart from low bulk density and mechanical durability, some authors have also found excessive nitrogen, sulfur, and chlorine as a consequence of the fertilization activity carried out in SRC plants [ 74 ]; however, this strongly depends on the plantation management adopted and on the specific characteristics of the growing site.…”
Section: Pellets From Alternative Forest Biomassmentioning
confidence: 99%
“…In addition, small-sized logs have the potential to produce pallets in secondary sawmills (Taipe and Rivas, 2021;Haro et al, 2015). According to Eisenbies et al (2021) and Latterini et al (2022), the demand for lignocellulosic biomass has increased for different paper industrial purposes.…”
Section: Origin Of Solid Waste Processingmentioning
confidence: 99%